The Role of Insulin Glargine and Human Insulin in the Regulation of Thyroid Proliferation Through Mitogenic Signaling - Sheng, Xiaoli; Yao, Kannan; Shao, Anwen; Tu, Sheng; Zhang, Xinxia; Chen, Ting; Yao, Dingguo (Frontiers in Endocrinology, 2019)
Our aim was to investigate whether human insulin (HI) or insulin glargine treatment could promote the proliferation of thyroid cells and determine the association between type 2 diabetes and thyroid disease. Rats were treated with different doses of HI and insulin glargine. Plasma glucose and the phosphorylation levels of the insulin receptor (IR), insulin-like growth factor 1 receptor (IGF-1R), protein kinase B (Akt), and extracellular signal-regulated kinase 1/2 (ERK1/2) were measured. A total of 105 rats were randomly assigned to three groups as follows: control group, HI group, and glargine group. Both drugs promoted the phosphorylation of IR, Akt, and ERK1/2 in a dose-dependent manner, and the effect of glargine persisted for longer period. Treatment with ultra-therapeutic doses of HI or glargine increased the expression of Ki-67 in thyroid cells. The results demonstrated that therapeutic doses of glargine have a longer-lasting hypoglycemic control than HI. Based on the results, HI or glargine did not stimulate thyroid cell proliferation at therapeutic doses, but high doses did.